Prevalence of self-medication in portuguese adolescents - Almeida, Inês (2022)
Self-medication is considered one of the health risk behaviors found among adolescents. The main objective of this study is to determine the prevalence of self-medication for portuguese adolescents. An observational cross-sectional study was carried out. The sample comprised 420 adolescents, of whom 343 (81.7%; 95%CI 77.8 – 85.2) had already self-medicated and 277 (66.0%; 95%CI 61.4 – 70.5) self-medicated in the last 6 months. The main health problems that motivated self-medication were headache (76.7%), flu (70.6%), sore throat (56%) and fever (54.5%). Paracetamol was the most consumed drug (86.9%) followed by Ibuprofen (83.1%). The pharmacy (87.8%) was the preferred place to purchase drugs, however, 221 adolescents (64.4%) reported that they self-medicated with the medicines they had at home. Of the adolescents who resorted to self-medication only 59.6% sought additional information about the drug and 53.9% referred to the package leaflet of the medicinal product as the main source of clarification. A significant portion of the respondents (84.3%) believed that self-medication might be acceptable to treat minor illnesses. It was observed that self-medication is a very common practice among adolescents, making it an extremely important issue to carry out more studies on this section of portuguese population due to scarcity of existing ones. These data can be used to define strategies for the dissemination of the rational use of the drug in adolescent population.